Information seeking-pattern of Nigerian textile market women and strategies for improvement (2015)
The study investigated the information seeking-pattern of Nigerian textile market women and strategies for improvement of which the study was an ex-post-facto type and adopted survey research design. Disproportional stratified random technique was used to select markets for the study while questionnaire was used to collect data to elicit information from 1556 respondents and data were analyzed with the aid of frequency counts, percentages, mean and standard deviation. Findings revealed that majority of textile market women in Nigeria had information needs and these needs were adequately recognised by them. Also, they often seek information about their businesses and other life related issues. Gender bias, culture, lack of adequate skills, attitude and lack of awareness are the major challenges facing textile market women in Nigeria. Adequate training for textile market women and making information relating to their experiences public are largely major strategies that can be used to improve the information seeking behaviour of these women.